PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KERJA KARYAWAN PADA CV MITRA SS PURBALINGGA - Ambarwati, Chofifah; Barima, Hima; Supriatin, Dyah (Perwira Journal of Economics & Business, 2024)
Increasing employee awereness about the importance of complying with regulations has an effect on encouraging employees to motivate themselves in carrying out the work provided by the company. A survey conducted by researchers at a company that produces false eyelashes in Purbalingga. this study aims to determine the effect of motivation and work discipline on employee performance at CV Mitra SS Purbalingga either partially or simultaneously. This study uses a descriptive quantititative approach. The population in this study was 246. The sampling technique was purposive sampling, the number of which was determined by the slovin formula of 71 respondens. Data was collected using a questionnaire that was distributed directly which was analyzed using multiple linear regression techniques which were carried out using the SPSS version 27 program. Based on the results of this study, partially motivation has a significant positive effect on employee performance, partially work discipline has a significant positive effect on employee performance. Simultan, motivation and work discipline jointly or simultaneously have an influence on employee performance at CV Mitra SS Purbalingga.